TINGKAT PENGETAHUAN TENTANG SEKS BEBAS PADA REMAJA KELAS XI DI SMA NEGERI 11 YOGYAKARTA TAHUN 2014 - Suherni; Anita Rahmawati (MEDIA ILMU KESEHATAN, 2016)
Background: Free sex has become more familiar to teenagers in today's life. This phenomenon occurs within many teenagers in junior and senior high schools, in big cities as well as in remote villages. Free sex may result in unwanted pregnancy, sexually transmitted infections, and social disruption in the society. Objective: This study aimed to determine the level of knowledge about free sex in adolescents. Methods: This research was conducted in April 2014, at SMA 11 Yogyakarta. The subjects were all students of class XI, consisted of 270 students. This study used a questionnaire as a measuring tool. Data analysis was performed with a univariate analysis. Results: Results showed that most respondents had adequate level of knowledge (81%), 17% had moderate level of knowledge and 2% have low level of knowledge about free sex. Conclusion: The level of knowledge about free sex in SMA Negeri 11 Yogyakarta students was majority adequate. Keywords: Knowledge Level, Teens, Free Sex